Gerir a diversidade: contributos da aprendizagem cooperativa para a construção de salas de aula inclusivas - Cláudia Tavares; Isabel Sanches (Universidade do Minho, 2013)
The action-research we have held at the primary education, in a school placed near the town of Tomar, in 2009-2010, under the master's degree in Special Education, was the starting point for writing this article. The research had as main objective to promote the successful learning of a heterogeneous group of students, where a child considered with longstanding special educational needs is included - diagnosis of galactosaemia and cognitive impairment. Starting from the educational context of a particular classroom of 2nd and 3rd grades, where we were working as special education teacher, we had created an inclusive learning environment for each student in the class. Through effective collaboration between fellow teachers, we generated changes in methodologies, breaking with some traditional practices in the classroom, when regular teachers and special education are in the same learning space. By a systematic implementation of cooperative learning strategies among students, and applying qualitative data gathering techniques of research, before and after the intervention - interview, naturalistic observation, sociometry and documental research -, we have increased the quality and quantity of learning and promoted another way of 'looking to' the difference.